PENINGKATAN KESEHATAN GIGI DAN MULUT SISWA DI LINGKUNGAN SEKOLAH DENGAN PEMBERDAYAAN GURU DI SEKOLAH DASAR NEGERI I DAWAN KALER KLUNGKUNG TAHUN 2016 - IGA Raiyanti; Sagung Agung Putri Dwiastuti; I Made Budi Artawa; I Gede Surya Kencana; Ni Nyoman Dewi Supariani (Jurnal Kesehatan Gigi (Dental Health Journal), 2018)
Oral health is integral to overall health as stated in the formulation of the achievement of the Millennium Development Goals (MDGs) years. 2015. The aim of this activity is to provide basic knowledge and skills in the field of oral health teachers SDN I DawanKaler both theoretically and practically. Event Service is located in Building society SDN I DawanKalerKlungkung with the number of participants as many as 12 people, has carried out training on Monday June 7, 2016. The method used is lectures, practice, question and answer, discussion and exercises as well as demosntrasi dental health maintenance.Based on the evaluation through a questionnaire it turns out there is an increased knowledge of participants pelatihan.dimana statistical test results obtained by t test p = 0.000 significant at alpha 5% seen any significant difference the average value of pre-test and post-test participants. It is expected also from this activity, the teacher can pass on the knowledge that has been gained to the students and to the community